Thickness Dependence of Critical Current Density in MgB2 Films Prepared by Thermal Evaporation Method - Yakinci, Z. D.; Aydogdu, Y. (Springer, 2011)
MgB2 films with the thickness of 350 to 1150 nm have been prepared on the Al2O3 (001) single crystal substrates from high purity B and Mg powder by the thermal evaporation method. Films were then heat treated ex-situ under Mg vapor at 950 A degrees C to achieve actual MgB2 stoichiometry. Thickness of the films, so the deposition time, was varied to investigate its influence on critical current density of the films. The films fabricated were analyzed by means of microstructural, transport, and magnetic properties. The best T (c) and T (zero) values were obtained to be 39.5 K and 38 K, respectively, and decreased with increasing the thickness. We found that the critical current density of the films prepared is highly thickness dependent. The maximum J(c)(mag) value was calculated to be 3.18x10(6) A cm(-2) at 10 K and zero field for 1150 nm thick films but dropped drastically by thickness.
Keywords: MgB2 superconductor; Ultrasonic spray pyrolysis; MgB2 thin films; Superconducting MgB2 films